Temporary ectopic banking as a treatment option for mangled thumb: a case report - Meisam Jafari Kafiabadi; Adel Ebrahimpour; Seyyed Hamidreza Ayatizadeh; Reza Fereidooni; Amirhossein Kamalinia; Mehrdad Sadighi; Farsad Biglari; Seyed Arman Moein (Journal of Medical Case Reports)
Abstract Background Management of the extensive soft tissue injuries remains a significant challenge in orthopedic and plastic reconstructive surgery. Since the thumb is responsible for 40% of the functions of the hand, saving and reconstructing a mangled thumb is essential for the patient’s future. Case presentation This case report describes the management of a severe occupational thumb injury in a 25-year-old white Persian male who sustained an occupational injury to his left thumb, resulting in extensive burn, crush injury to the distal and proximal phalanx, and severe soft tissue damage to the first metacarpal, thenar, and palmar areas. Necrosis necessitated amputation through the first metacarpophalangeal joint. Postdebridement observation revealed a viable first metacarpal bone but was exposed due to a lack of soft tissue. Given the wound contamination and infection risk, the first metacarpal bone was banked in the distal forearm. After a 4 week period of antibiotics, irrigation, debridement, and vacuum dressing, the thumb and soft tissue reconstruction were performed, retrieving the viable first metacarpal. The first metacarpophalangeal joint fusion was achieved with an intramedullary screw and two K-wires. A reverse adipofascial radial artery forearm flap and skin grafts from the left thigh were used for soft tissue reconstruction. Conclusion This case highlights the importance of a flexible, staged approach to hand trauma, emphasizing the utility of ectopic banking and reconstructive techniques in managing complex hand injuries. This report contributes to the ongoing dialogue on optimal strategies for hand reconstruction, particularly in cases where traditional immediate reconstruction is not feasible.